Early self-reported post-traumatic stress symptoms after trauma exposure and associations with diagnosis of post-traumatic stress disorder at 3 months: latent profile analysis. Issue 1 (26th January 2023) - Shih, Chia-Hao; Zhou, Adrian; Grider, Stephen; Xie, Hong; Wang, Xin; Elhai, Jon D.
Abstract : Background: Trauma exposure can cause post-traumatic stress symptoms (PTSS), and persistently experiencing PTSS may lead to the development of post-traumatic stress disorder (PTSD). Research has shown that PTSS that emerged within days of trauma was a robust predictor of PTSD development. Aims: To investigate patterns of early stress responses to trauma and their associations with development of PTSD. Method: We recruited 247 civilian trauma survivors from a local hospital emergency department. The PTSD Checklist for DSM-5 (PCL-5) and Acute Stress Disorder Scale (ASDS) were completed within 2 weeks after the traumatic event. Additionally, 3 months post-trauma 146 of these participants completed a PTSD diagnostic interview using the Clinician Administered PTSD Scale for DSM-5. Results: We first used latent profile analysis on four symptom clusters of the PCL-5 and the dissociation symptom cluster of the ASDS and determined that a four-profile model ('severe symptoms', 'moderate symptoms', 'mild symptoms', 'minimal symptoms') was optimal based on multiple fit indices. Gender was found to be predictive of profile membership. We then found a significant association between subgroup membership and PTSD diagnosis ( χ 2 (3) = 11.85, P < 0.01, Cramer's V = 0.263). Post hoc analysis revealed that this association was driven by participants in the 'severe symptoms' profile, who had a greater likelihood of developing PTSD. Conclusions: These findings fill the knowledge gap of identifying possible subgroups of individuals based on their PTSS severity during the early post-trauma period and investigating the relationship between subgroup membership and PTSD development, which have important implications for clinical practice.